Experimental and analytical study on dynamic performance of timber-concrete composite beams. (30th January 2015) - Rijal, Rajendra; Samali, Bijan; Shrestha, Rijun; Crews, Keith
Highlights: Experimental and analytical dynamic investigation of four full-scale TCC beams. Performed impact hammer tests on the TCC beams with three different connections. The fundamental frequency of all tested beams was above 8 Hz, which is acceptable. Analytical models predicted frequency of all beams within acceptable range of ±8%. Beam-3 with six bird-mouth notches showed best dynamic performance. Abstract: Timber-concrete composite (TCC) construction provides an effective and efficient solution for long-span floors in multi-storey buildings. Because of the light-weight and long-span of the floors, the design of these floors are normally governed by serviceability criteria such as deflection, vibration, acoustic, etc and design for strength limits are generally not an issue. Floor vibration caused by dynamic actions such as people walking on the floor, machinery or any similar repetitive actions may not only cause discomfort to occupants but may also result in structural failure as a result of resonance. However, limited design guidance is available in the design codes to address the vibration behaviour of TCC floors owing to a lack of reliable performance data and as such, there is a need to undertake further research into the behaviour of TCC floors. This paper reports on the tests performed on four identical TCC beams, which represent part of a floor system, with different shear connector arrangements, to assess their dynamic performance under the application of impact action using modal parameters (natural frequencies, damping ratios and mode shapes). Five analytical models are used to predict natural frequency of the beams and their reliability is checked.